BENTUK KOMUNIKASI PEMASARAN PADA BISNIS RETAIL: STUDI DESKRIPTIF KOMPARATIF PADA INDOMARET DAN ALFAMART DI SURABAYA - Aini, Yuli Nur; Handoko, Rudy; Tjahjono, Endro (Universitas 17 Agustus 1945 Surabaya, 2015)
Traders are dealers who have climbed down distribution market share, this is what makes Indonesiahas very much at all merchants, one Indomaret and Alfamart, see the closeness of those who are sointense, the forms of communication that they use, is one way to maintain their existence. Starting fromPromo Price, Discount, marchendise, until the message across, Indomaret and Alfamart do. Seeing thisphenomenon the authors wanted to find out what forms of marketing communication used by Alfamartand Indomaret and what the impact of proximity between Indomaret and Alfamart. This research usesdescriptive qualitative comparative study, where this research aimed to determine the forms of marketingcommunication used by Alfamart and Indomaret and to determine the impact of proximity betweenIndomaret and Alfamart.Keywords: forms of marketing communication, Alfamart and Indomaret.